Stomata as the Main Pathway for the Penetration of Atmospheric Particulate Matter Pb into Wheat Leaves - Ke Zhang; Yujing Liang; Chuang Ma; Haopeng Guo; Fuyong Liu; Aihua Gao; Nan Liu; Hongzhong Zhang (Toxics)
The absorption of atmospheric particulate matter lead (APM-Pb) by wheat leaves is the primary source of Pb in wheat grains, yet the mechanisms of how wheat leaves absorb Pb remain unclear. In this study, spraying Pb(NO3)2 (Treatment T1) and spraying PbS (Treatment T2) were used as soluble and insoluble Pb, respectively, to evaluate the primary pathways of APM-Pb absorption by wheat leaves, as well as the translocation and accumulation patterns of Pb within the wheat plant. The results showed that both soluble and insoluble Pb can be absorbed by wheat leaves. Compared to the control group (CK), the treatment of T1 and T2 significantly increased Pb concentration in both leaves and grains, as well as the Pb accumulation rate in grains (p < 0.05). Scanning electron microscopy–energy dispersive spectrometry (SEM-EDS) technology visually confirmed the distribution of particulate Pb in the stomatal region, demonstrating that solid-state Pb can penetrate the leaves through stomata. From the greening stage (GS) to the late filling stage (FS2), the leaves’ cell sap contained the highest proportion of Pb, indicating that Pb within the cell sap possesses the greatest capacity for translocation. Concurrently, a significant increase in grain Pb concentration during this period indicated that the migration of Pb to cell sap after penetrating the leaves is subsequently translocated to the grains (p < 0.05). Compared to the jointing stage (JS), the proportion of the ethanol and water extraction states of Pb significantly decreased in FS2 (p < 0.05), indicating that Pb is more readily translocated to the grains during this period. Moreover, in FS2, Pb concentration in leaves and grains in the T2 treatment reached 76.5% and 63.9% that of T1, respectively. Since PbS can only be absorbed through stomata, it can be inferred that stomata are the primary pathway for wheat leaves to absorb APM-Pb. Therefore, Pb absorbed through the stomatal pathway and accumulated in the cell sap fraction is most likely to be translocated to the grains during the filling stage. This study provides new insights into the mechanisms of Pb absorption and translocation in wheat, emphasizing the critical role of stomata in the uptake of APM-Pb. It offers a new direction for breeding wheat varieties resistant to APM-Pb pollution, which is of significant importance in agricultural practices aimed at reducing heavy metal contamination in crops.